2021
DOI: 10.1097/pr9.0000000000000923
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial pain in 1916 patients with early or moderate Parkinson disease

Abstract: This article reports the largest epidemiological study of orofacial pain prevalence in patients with Parkinson disease to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…In total, nine studies reported unspecified pain in the orofacial area (Adewusi et al, 2018 ; Agrawal et al, 2021 ; Behari et al, 2020 ; Bonenfant et al, 2016 ; de Mattos et al, 2019 ; García et al, 2021 ; Martinez‐Martin et al, 2017 ; O'Neill et al, 2021 ; Rodríguez‐Violante et al, 2017 ), of which two included a control group (Adewusi et al, 2018 ; Martinez‐Martin et al, 2017 ). The within‐group results showed prevalences that varied between 12 and 74%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, nine studies reported unspecified pain in the orofacial area (Adewusi et al, 2018 ; Agrawal et al, 2021 ; Behari et al, 2020 ; Bonenfant et al, 2016 ; de Mattos et al, 2019 ; García et al, 2021 ; Martinez‐Martin et al, 2017 ; O'Neill et al, 2021 ; Rodríguez‐Violante et al, 2017 ), of which two included a control group (Adewusi et al, 2018 ; Martinez‐Martin et al, 2017 ). The within‐group results showed prevalences that varied between 12 and 74%.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 studies that examined TMD pain (Bakke et al, 2011 ; Behari et al, 2020 ; Bonenfant et al, 2016 ; de Mattos et al, 2019 ; Martinez‐Martin et al, 2017 ; Mylius et al, 2021 ; O'Neill et al, 2021 ; Persson et al, 1992 ; Verhoeff et al, 2018 ; Verhoeff et al, 2022 ; Wooten Watts et al, 1999 ), five studies included a control group (Bakke et al, 2011 ; Martinez‐Martin et al, 2017 ; Persson et al, 1992 ; Verhoeff et al, 2018 ; Wooten Watts et al, 1999 ). The within‐group results showed prevalences that varied between 0 and 33%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can increase the incidence of dental pathology, resulting in, for example, dental pain and, therefore, reduced quality of life. Besides, O’Neill et al (2021) reported a prevalence of orofacial pain in PD patients of 7.3%, associated with oral motor dysfunction 26 . Orofacial pain can greatly influence vital human needs like eating and chewing, which can have a negative impact on the quality of life of those who suffer from orofacial pain 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, O’Neill et al (2021) reported a prevalence of orofacial pain in PD patients of 7.3%, associated with oral motor dysfunction. 26 Orofacial pain can greatly influence vital human needs like eating and chewing, which can have a negative impact on the quality of life of those who suffer from orofacial pain. 27 It would be logical to suggest that when people experience and report a deteriorated oral health, they would also report a worsened OHRQoL.…”
Section: Discussionmentioning
confidence: 99%